University Community Service in the context of the pandemic from the perspective of the students of the Pacific Campus of the Universidad de Costa Rica - Salas Alvarado, Jonnathan (2023)
The pandemic caused by SARS-CoV-2 in 2020 generated changes and uncertainty throughout the world. All areas of human life were affected at that time. The university community service (TCU) of the Universidad de Costa Rica, of course, was no exception. The institution ordered the virtualization of all its processes, which meant important variations in the work methodology for both teachers and students. This article systematizes the experience of 49 students from the Pacific campus of the Universidad de Costa Rica who were enrolled in the university community service project TC-578: Promotion of healthy lifestyles and healthy coexistence. These students had to carry out their community service during the pandemic in a virtual way. The article aims to obtain information from the perspective of the students, mainly in relation to the challenge that the development of this project represented for them. It is possible to establish a bit of the reality of each of the participants of the study, as well as their experience and opinions regarding the effectiveness of virtuality when working with vulnerable communities.